Postcolonial Identity of Kazakhstan : Subalternity and Empire in the Russian-Kazakh Relations - Shakhanova, Gaziza (2020)
This dissertation aims to explore the postcolonial identity of Kazakhstan, which has developed in relation with its historical and political Other, Russia. I argue that Kazakhstan is a subaltern country and that it is its own political elites who relegate the country to a position subordinated to Russia. It is not new in IR to examine Kazakhstan as a postcolonial country or Russia as an empire. However, the country’s subalternity, which concerns various aspects of the current political, economic, and social life, has not yet been properly reflected. This subalternity is indicated by the similarity of state policies, by the Kazakh state authorities apparently emulating the reformative policies of Russia, by the absence of any criticism of contemporary Russia on the official level, or by the extent to which both the state authorities and population find it comfortable to be tuned into the Russian episteme. It is this subaltern status of the country, forged by the Kazakh state authorities and recognized by the local elites, which I explore in this thesis.